Measurement of the Michel parameters and the average τ neutrino helicity from τ decays in e+e- → τ+τ- - Dova, María Teresa (1996)
The Michel parameters ϱ, η, ξ, and ξδ, the chirality parameter ξh and the τ polarization Pτ are measured using 32012 τ pair decays. Their values are extracted from the energy spectra of leptons and hadrons in <mtext>τ</mtext>−<mtext> → l</mtext>−<mtext>ν</mtext>l<mtext>ν</mtext>τ and τ− → π−ντ decays, the energy and decay angular distributions in τ− → ϱ−ντ decays, and the correlations in the energy spectra and angular distributions of the decay products. Assuming universality in leptonic and semileptonic τ decays, the results are ϱ = 0.794±0.039±0.031, η = 0.25±0.17±0.11, ξ = 0.94±0.21±0.07, ξδ = 0.81±0.14±0.06, ξh = −0.970±0.053±0.011, and Pτ = −0.154±0.018±0.012. The measurement is in agreement with the V-A hypothesis for the weak charged current.